El trabajo asalariado: La mecanización del espíritu (2019)
Wage labor has not been a novelty in the development of Western history. However, this category has become more and more important over the last two centuries, generating contradictory intellectual positions. Embodied in different authors, these positions materialized in speeches, sometimes apologetic and some others decidedly critical, in which the social, cultural and human consequences of a society shaped around wage labor and the industrialization process where it flourished, are denounced. Some characteristics of work and the conditions of its possibility emerged with modern Western society and converged in the development of the industrialized world, giving wage labor a privileged status in the economic and administrative reflection. This article explores the situation described above, denouncing the mechanization of the spirit of the employee when trying to be efficient; understanding efficiency as the engine of the ideal of progress over the last one hundred years.